Broad orthogonal distribution polyethylene for film

By using a polyethylene and a specific catalyst system with a wide orthogonal composition distribution, the trade-off problem of polyethylene films between performance properties is solved, and high stiffness, toughness, processability and optical performance are achieved.

CN115605518BActive Publication Date: 2025-03-25EXXONMOBIL CHEMICAL PATENTS INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080087724.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-17
Filing Date
2020-11-18
Publication Date
2025-03-25
Estimated Expiration
2040-11-18

AI Technical Summary

Technical Problem

When developing new polyethylene products, it is difficult to take into account strength, toughness, processability and optical properties in a composition, and improving toughness usually reduces processability and affects optical properties.

Method used

Polyethylene with a wide orthogonal composition distribution (BOCD) is used to produce through a mixed catalyst system, including racemic-dimethylsilyl bis(tetrahydroindenyl) zirconium dichloride catalyst and zirconium cocatalyst, and the reaction conditions such as temperature, pressure and comonomer content are adjusted to prepare polyethylene with a specific density and molecular weight distribution.

Benefits of technology

The ideal combination of polyethylene film in terms of stiffness, toughness, processability and optical properties is achieved, improving the mechanical properties and processability of the film, while maintaining good optical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003697611620000051
    Figure BDA0003697611620000051
  • Figure BDA0003697611620000061
    Figure BDA0003697611620000061
  • Figure BDA0003697611620000071
    Figure BDA0003697611620000071
Patent Text Reader

Abstract

Comprising ethylene-derived units and 0.5wt% to 10wt% of C3-C 12 Polyethylene containing α-olefin derived units can be synthesized using a mixed catalyst comprising racemic dimethylsilyl bis(tetrahydroindenyl) zirconium dichloride and a zirconium co-catalyst in a molar ratio of 50:50-90:10, and wherein the zirconium co-catalyst is a poor comonomer binder compared to the racemic dimethylsilyl bis(tetrahydroindenyl) zirconium dichloride catalyst. Such polyethylene can have a molecular weight of 0.91 g / cm 3 ‑0.93g / cm 3 Density, I2 value of 0.5g / 10min‑2g / 10min, I of 25g / 10min‑75g / 10min 21 Value, 25‑75 I 21 / I2 ratio, a molar reverse comonomer index (RCI,m) of 30-180, a phase angle equal to or lower than 70° at a complex modulus G* of 10,000 Pa, a θ2 of 1.5 radians to -1.5 radians, and a low density population of 50 wt% to 70 wt% of the polyethylene.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Application No. 62 / 949,241, filed on December 17, 2019, entitled “Wide Orthogonal Distribution Polyethylene for Films,” the entire contents of which are incorporated herein by reference.

[0003] field

[0004] The present disclosure relates to polyethylenes useful for films.

[0005] background

[0006] There are trade-offs between various performance attributes, which has always been a major obstacle in the development of new polyethylene product technologies. Such performance attributes include a combination of stiffness, toughness, processability and optical properties, all of which are important for most linear low-density polyethylene (LLDPE) film applications. However, it is difficult to achieve all of these attributes in one composition because improving toughness often reduces processability and increases stiffness which can lead to compromised optical properties. SUMMARY OF THE INVENTION

[0008] The present disclosure relates to polyethylenes useful for films, and more particularly to films made from polyethylenes having a broad orthogonal composition (or comonomer) distribution (BOCD).

[0009] A non-limiting example embodiment of the present disclosure is a method comprising: reacting ethylene, C3 to C 12 An alpha-olefin comonomer and hydrogen are reacted in the presence of a mixed catalyst to form a polyethylene, wherein the polyethylene comprises ethylene-derived units and C3-C4-C6-H2O in an amount of 0.5 wt % to 10 wt % of the polyethylene. 12 α-olefin derived units, wherein the polyethylene has: 0.91 g / cm 3 -0.93g / cm 3 Density, I2 value in the range of 0.5g / 10min-2g / 10min, I in the range of 25g / 10min-75g / 10min 21 Value, 25-75 I 21 / I2 ratio, a molar reverse comonomer index (RCI,m) of 30-180, a phase angle equal to or lower than 70° at a complex modulus G* of 10,000 Pa, θ2 in the range of 1.5 radians to -1.5 radians, and a low density population in the range of 50 wt% to 70 wt% of the polyethylene; and wherein the mixed catalyst comprises racemic-dimethylsilylbis(tetrahydroindenyl)zirconium dichloride (Compound I) and a zirconium co-catalyst (Compound II), the molar ratio of Compound I to Compound II being 50:50 to 90:10, and wherein the zirconium co-catalyst is a poor comonomer binder compared to the racemic-dimethylsilylbis(tetrahydroindenyl)zirconium dichloride catalyst. The reaction conditions may include one or more of the following: wherein the reaction temperature is from 66°C (150°F) to 93°C (200°F); wherein the reactor pressure is from 200 psig to 400 psig; wherein the mole % ratio of comonomer to ethylene in the reactor is from 0.005 to 0.030; and wherein the mole % ratio of hydrogen to ethylene in the reactor is from 3.0 to 5.5.

[0010] Another non-limiting example embodiment is a film comprising: a C3-C6 polyethylene having ethylene-derived units and an amount of 0.5 wt % to 10 wt % of the polyethylene. 12 A polyethylene containing alpha-olefin derived units, the polyethylene having: 0.91 g / cm 3 -0.93g / cm 3 Density, I2 value in the range of 0.5g / 10min-2g / 10min, I in the range of 25g / 10min-75g / 10min 21 Value, 25-75 I 21 / I2 ratio, a molar reverse comonomer index (RCI,m) of 30-180, a phase angle equal to or less than 70° at a complex modulus G* of 10,000 Pa, θ2 in the range of 1.5 radians to -1.5 radians, and a low density population in the range of 50 wt% to 70 wt% of the polyethylene; wherein the film has a machine direction (MD) 1% secant flexural modulus of 25,000 psi to 45,000 psi, a machine direction Elmendorf tear of 200 g to 350 g, and a dart drop impact value of 200 g / mil to 1,000 g / mil. The film may also have one or more of the following properties: wherein the film has a longitudinal tensile yield strength of 1,000psi-2,000psi; wherein the film has a TD 1% secant flexural modulus of 30,000psi-60,000psi; wherein the film has a TD tensile yield strength of 1,000psi-2,500psi; wherein the film has a longitudinal elongation at yield of 5%-12%; wherein the film has a longitudinal tensile strength of 5,000psi-10,000psi; and wherein the film has a longitudinal elongation at break of 400%-550%.

[0011] Yet another non-limiting example of the present disclosure is a composition comprising: a C3-C6-ethylene-containing unit and an amount of 0.5 wt % to 10 wt % of the polyethylene; 12 A polyethylene containing alpha-olefin derived units, the polyethylene having: 0.91 g / cm 3 -0.93g / cm 3 Density, I2 value in the range of 0.5g / 10min-2g / 10min, I in the range of 25g / 10min-75g / 10min 21 Value, 25-75 I 21 / I2 ratio, a molar reverse comonomer index (RCI,m) of 30-180, a phase angle equal to or lower than 70° at a complex modulus G* of 10,000 Pa, θ2 in the range of 1.5 radians to -1.5 radians, and a low density population in the range of 50 wt% to 70 wt% of the polyethylene.

[0012] BRIEF DESCRIPTION OF THE DRAWINGS

[0013] The following drawings are included to illustrate certain aspects of the embodiments and should not be construed as exclusive embodiments. The disclosed subject matter is capable of considerable modification, alteration, combination, and equivalent substitutions in form and function, as will be made by those skilled in the art having the benefit of this disclosure.

[0014] Figure 1 and 2are cross fractionation chromatography (CFC) data for the two polyethylenes described herein.

[0015] Figure 3 The orientation index describing the direction in molecular space that each single peak points to is shown. A has an orientation of 0 (it could also be 180) and would be described as having a broad molecular weight distribution (MWD) and a narrow composition distribution (CD). B has an orientation of 45 and would be described as having a broad orthogonal composition distribution. C has an orientation of 90 and would be described as having a narrow MWD and a broad CD. D has an orientation of 135 and would be described as conventional. Although individual peaks can point in different directions, the overall sample can have completely different orientations, such as MWD and CD. p1 , M p2 , T p1 , and T p2 As described.

[0016] Detailed Description

[0017] The present disclosure relates to polyethylenes useful for films, and more particularly to films prepared from polyethylenes having a broad orthogonal composition (or comonomer) distribution (BOCD).

[0018] Without being bound by theory, it is believed that the above-mentioned trade-offs in performance attributes can be significantly overcome by adjusting the molecular weight and comonomer distribution of the polyethylene product. The present invention includes polyethylene produced by a mixed catalyst system. More specifically, the mixed catalyst system includes a racemic-dimethylsilylbis(tetrahydroindenyl)zirconium dichloride catalyst and a zirconium co-catalyst that is a poor comonomer binder compared to the racemic-dimethylsilylbis(tetrahydroindenyl)zirconium dichloride catalyst. That is, the racemic-dimethylsilylbis(tetrahydroindenyl)zirconium dichloride catalyst incorporates comonomers into polyethylene to a greater extent than the zirconium co-catalyst. Therefore, the polyethylene population produced by the racemic-dimethylsilylbis(tetrahydroindenyl)zirconium dichloride catalyst has a lower density than the polyethylene population produced by the zirconium co-catalyst. The resulting overall polyethylene product has a BOCD polyethylene product having (1) low weight average molecular weight (Mw) and high density polyethylene chain populations and (2) a combination of high Mw and low density polyethylene chain populations, which achieves a combination of desirable performance attributes.

[0019] The relatively low density BOCD type polyethylene described herein is a polyethylene product that is multimodal in terms of molecular weight and short chain branching. This is achieved using a combined catalyst system in which a catalyst with poor comonomer bonding is combined with a catalyst with high comonomer bonding in a gas phase process to produce a multimodal polyethylene with a desired BOCD. Such polyethylene is very useful in forming films such as cast or blown films, especially blown films formed by melt extruding the polyethylene into sheets or cylindrical / tubular forms and exposing to positive air pressure for the formed film to expand the sheet transversely and longitudinally (TD and MD) (with or without some longitudinal and transverse (TD) tension, stretching the material before or during cooling). The polyethylene of the present invention can also be used for extrusion coating applications.

[0020] The term "film" as used herein refers to a continuous, flat, preferably flexible polymer structure having an average thickness in the range of 1 μm to 250 μm (alternatively 5 μm to 200 μm, alternatively 10 μm to 100 μm), or such a coating of similar thickness attached to a flexible, non-flexible or otherwise solid structure. The "film" may comprise one or more layers, each of which may comprise the polyethylene of the present invention. For example, one or more "film" layers may comprise a mixture of polyethylene and LDPE, another LLDPE, a polypropylene homopolymer and copolymer, or a plastomer (e.g., a polyethylene copolymer with a high comonomer content). Ideal uses for such films include label and packaging applications and stretch and cling films for wrapping commercial items.

[0021] As used herein, when a polymer is referred to as comprising a monomer, the monomer is present in the polymer in the polymerized form of the monomer or in a derived form of the monomer. As used herein, the term "derived units" refers to the polymerized form of the monomer from which the polymer is derived. For example, when a polymer is said to have an "ethylene" content of 95 wt% to 99.5 wt%, it is understood that the mer units in the polymer are derived from ethylene in the polymerization reaction and the derived units are present in an amount of 95 wt% to 99.5 wt%, based on the weight of the polymer.

[0022] Table 1 provides a list of the test methods used for the various measurements described herein.

[0023] Table 1

[0024]

[0025]

[0026] 1 H NMR data were taken at 393 K in a 10 mm probe 1The H frequency was collected on a Bruker spectrometer (available from Agilent Technologies, Santa Clara, CA.) with a minimum of 400 MHz. Data were recorded using a maximum pulse width of 45°C, a pulse interval of 5 seconds, and 512 transient signal averages. The spectral signal was integrated and the number of unsaturated types per 1,000 carbons was calculated by multiplying the different groups by 1,000 and dividing the result by the total number of carbons. The number average molecular weight (Mn) was calculated by dividing the total number of unsaturated species by 14,000 in g / mol.

[0027] The GPC 4D program for molecular weight and comonomer composition distribution is completed by GPC-IR connected to multiple detectors. Unless otherwise specified, the distribution and moment (Mw, Mn, Mz, Mw / Mn, etc.) of molecular weight and comonomer content (C2, C3, C6, etc.) are determined using a high temperature gel permeation chromatograph (Polymer Char GPC-IR), which is equipped with an infrared detector assembly IR5, an 18-angle light scattering detector and a viscometer based on a multi-channel band filter. Three Agilent PLgel 10-μm mixed BLS columns are used to provide polymer separation. Aldrich reagent grade 1,2,4-trichlorobenzene (TCB) containing 300ppm antioxidant butylated hydroxytoluene (BHT) is used as a mobile phase. The TCB mixture is filtered through a 0.1 micron Teflon filter and degassed with an online degasser before entering the GPC instrument. The nominal flow rate is 1.0mL / min, and the nominal injection volume is 200μL. The entire system, including the transfer line, column and detector, is contained in an oven maintained at 145°C. The polymer sample is weighed and sealed in a standard vial, to which 80 μL of flow marker (heptane) is added. After the vial is loaded into the autosampler, the polymer is automatically dissolved in the instrument with 8 mL of added TCB solvent. For most polyethylene samples, the polymer is dissolved by continuous shaking at 160°C for about 1 hour, or for polypropylene samples, the polymer is dissolved by continuous shaking at 160°C for about 2 hours. The TCB density used in the concentration calculation is 1.463 g / ml at room temperature and 1.284 g / mL at 145°C. The sample solution concentration is 0.2-2.0 mg / ml, with lower concentrations used for samples with higher molecular weights. The concentration (c) at each point in the chromatogram is calculated by the IR5 broadband signal intensity (I) subtracted from the baseline using the following formula: c=βI, where β is the mass constant. The mass recovery rate can be calculated from the ratio of the integral area of ​​the concentration chromatogram in the elution volume to the injection mass equal to the predetermined concentration multiplied by the injection loop volume. Conventional molecular weight (IR molecular weight) is determined by combining a universal calibration relationship with a column calibration using a series of monodisperse polystyrene (PS) standards ranging from 700 g / mol to 10,000,000 gm / mol. The molecular weight for each elution volume is calculated using equation (3):

[0028]

[0029] The variables with the subscript "PS" represent polystyrene, while the variables without the subscript represent the test sample. PS =0.67 and K PS=0.000175, α and K for other materials are calculated as published in the literature (see Sun, T. et al. (2001) "Macromolecules, v.34, pg.6812), but for the present invention and claims, for linear ethylene polymers, α = 0.695 and K = 0.000579; for linear propylene polymers, α = 0.705 and K = 0.0002288; for linear butene polymers, α = 0.695 and K = 0.000181; for ethylene-butene copolymers, α is 0.695 and K is 0.000579*(1-0.0087*w2b+0.000018*(w2b) 2 ), where w2b is the total weight percent of butene comonomer; for ethylene-hexene copolymers, α is 0.695 and K is 0.000579*(1-0.0075*w2b), where w2b is the total weight percent of hexene comonomer; for ethylene-octene copolymers, α is 0.695 and K is 0.000579*(1-0.0077*w2b), where w2b is the total weight percent of octene comonomer. Unless otherwise stated, concentrations are in g / cm 3 The molecular weight is expressed in g / mol and the intrinsic viscosity (and therefore K in the Mark-Houwink equation) is expressed in dL / g.

[0030] The comonomer composition is determined by the ratio of the IR5 detector intensities corresponding to the CH2 and CH3 channels, calibrated with a series of polyethylene and polypropylene homopolymer / copolymer standards whose nominal values ​​are predetermined by NMR or FTIR. In particular, this provides the number of methyl groups per 1,000 total carbons as a function of molecular weight (CH3 / 1,000TC). The short chain branch (SCB) content per 1,000TC as a function of molecular weight is then calculated by applying a chain end correction to the CH3 / 1,000TC function, assuming that each chain is linear and terminated by a methyl group at each end (SCB / 1,000TC). The weight percentage of the comonomer is then obtained from the following expression, where f is 0.3, 0.4, 0.6, 0.8, etc., for comonomers such as C3, C4, C6, C8, etc.:

[0031] w2=f*SCB / 1000TC (4)

[0032] The overall composition of the polymer from GPC-IR and GPC-4D analysis is obtained by considering the entire signal of the CH3 and CH2 channels between the integration limits of the concentration chromatogram. First, the following ratio is obtained:

[0033]

[0034] The CH3 and CH2 signal ratios are then subjected to the same calibration as previously mentioned in obtaining CH3 / 1,000TC as a function of molecular weight to obtain total CH3 / 1,000TC. The total number of methyl chain ends per 1,000TC (total number of CH3 ends / 1,000TC) is obtained by weight averaging the chain end correction over the molecular weight range. Then,

[0035] w2b=f*total CH3 / 1,000TC (6)

[0036] Total SCB / 1,000TC=total CH3 / 1,000TC-total number of CH3 terminals / 1,000TC (7) and total SCB / 1,000TC is converted to total w2 in the same manner as above.

[0037] The LS detector was an 18-angle Wyatt Technology High Temperature DAWN HELEOS II. The LS molecular weight (M) at each point in the chromatogram was determined by analyzing the LS output using the Zimm model for static light scattering (Light Scattering from Polymer Solutions; Huglin, MB, Ed.; Academic Press, 1972):

[0038]

[0039] Here, ΔR(θ) is the hyper-Rayleigh scattering intensity measured at the scattering angle θ, c is the polymer concentration determined by IR5 analysis, A2 is the second virial coefficient, P(θ) is the morphology factor of the monodisperse random coils, and Ko is the optical constant of the system:

[0040]

[0041] Where NA is Avogadro's number, and (dn / dc) is the refractive index increment of the system. The refractive index of TCB at 145°C and λ=665nm is n=1.500. For the analysis of polyethylene homopolymers, ethylene-hexene copolymers and ethylene-octene copolymers, dn / dc=0.1048 ml / mg and A2=0.0015; for the analysis of ethylene-butene copolymers, dn / dc=0.1048*(1-0.00126*w2) ml / mg and A2=0.0015, where w2 is the weight percent of butene comonomer.

[0042] The specific viscosity is determined using a high temperature Agilent (or Viscotek Corporation) viscometer having four capillaries arranged in a Wheatstone bridge configuration and having two pressure sensors. One sensor measures the total pressure drop across the detector and the other sensor located between the two sides of the bridge measures the differential pressure. The specific viscosity ηs of the solution flowing through the viscometer is calculated from their output. The intrinsic viscosity [η] at each point in the chromatogram is calculated by the following formula: [η] = ηs / c, where c is the concentration and is determined by the IR5 broadband channel output. The viscosity MW at each point is calculated as where α ps is 0.67 and K ps It is 0.000175.

[0043] The reverse comonomer index (RCI, m) is calculated from x2 (mol% comonomer C3, C4, C6, C8, etc.) as a function of molecular weight, where x2 is obtained from the following expression, where n is the number of carbon atoms in the comonomer (3 for C3, 4 for C4, 6 for C6, etc.):

[0044]

[0045] The molecular weight distribution W(z) (where z = log 10 M) is modified to W'(z); this is to effectively remove points with low signal-to-noise ratio in the composition signal. In addition, points with W' below 2000 g / mole are set to 0.

[0046] Then W′ is renormalized so that

[0047]

[0048] The modified weight average molecular weight (M) is calculated within the effectively reduced molecular weight range as follows: w ′):

[0049]

[0050] Then calculate RCI,m:

[0051]

[0052] The reverse comonomer index (RCI,w) is also defined based on the weight fraction comonomer signal (w2 / 100) and is calculated as follows:

[0053]

[0054] Note that in the above definite integral, the limits of integration are the widest possible limits for reasons of generality; however, in reality the function is only integrated over the limited range in which the data are taken, and the rest of the range in which the data are not taken is considered to be 0. Furthermore, due to the way W' is obtained, it is possible that W' is a discontinuous function and the above integral needs to be performed piecewise.

[0055] Three comonomer distribution ratios are also defined based on the weight percent (w2) comonomer signal and are denoted as CDR-1,w, CDR-2,w and CDR-3,w as follows:

[0056]

[0057]

[0058]

[0059] Wherein w2(Mw) is the weight percent comonomer signal corresponding to the molecular weight of Mw, w2(Mz) is the weight percent comonomer signal corresponding to the molecular weight of Mz, w2[(Mw+Mn) / 2)] is the weight percent comonomer signal corresponding to the molecular weight of (Mw+Mn) / 2, and w2[(Mz+Mw) / 2] is the weight percent comonomer signal corresponding to the molecular weight of Mz+Mw / 2, where Mw is the weight average molecular weight, Mn is the number average molecular weight, and Mz is the z-average molecular weight.

[0060] Therefore, the comonomer distribution ratio can also be defined using the molar percentage comonomer signals, CDR-1, m, CDR-2, m and CDR-3, m respectively:

[0061]

[0062]

[0063]

[0064] Where x2(Mw) is the mole percent comonomer signal corresponding to the molecular weight of Mw, x2(Mz) is the mole percent comonomer signal corresponding to the molecular weight of Mz, x2[(Mw+Mn) / 2)] is the mole percent comonomer signal corresponding to the molecular weight of (Mw+Mn) / 2, and x2[(Mz+Mw) / 2] is the mole percent comonomer signal corresponding to the molecular weight of Mz+Mw / 2, where Mw is the weight average molecular weight, Mn is the number average molecular weight, and Mz is the z-average molecular weight.

[0065] SAOS rheology testing uses an Advanced Rheometrics Expansion System (ARES) to measure dynamic shear melt rheology data at 190°C using parallel plates (diameter = 25 mm) using original compression molded samples at each temperature. The measurements were performed at angular frequencies ranging from 0.01 rad / s to 100 rad / s. Depending on the molecular weight and temperature, strains of 10% and 15% were used and the linearity of the response was verified. A stream of nitrogen was circulated through the sample oven to minimize chain extension or crosslinking during the experiment. All samples were compression molded at 190°C without the addition of stabilizers. A sinusoidal shear strain was applied to the material. If the strain amplitude is small enough, the material behaves linearly.

[0066] The bimodal polyethylene was subjected to cross fractionation chromatography (CFC) on a CFC-2 instrument from Polymer Char, Valencia, Spain, which combines TREF and conventional GPC (TREF / GPC), as disclosed in WO 2015 / 123164 A1. The instrument was operated and the data were subsequently processed, such as smoothing parameters, setting baselines and defining integration limits, as described in the CFC user manual provided with the instrument or in a manner commonly used in the art. The instrument was equipped with a TREF column (stainless steel; 3 / 8" outer diameter; 15 cm length; filler is non-porous stainless steel microspheres) in the first dimension and a GPC column set (3xPLgel 10μm Mixed B columns, obtained from Polymer Labs, UK) in the second dimension. Downstream of the GPC column is an infrared detector (IR4 from PolymerChar) capable of generating an absorbance signal proportional to the polymer concentration in the solution.

[0067] The sample to be analyzed was dissolved in o-dichlorobenzene at a concentration of about 5 mg / ml by stirring at 150°C for 75 minutes. A volume of 0.5 ml of the solution containing 2.5 mg of polymer was then loaded into the center of the TREF column, the column temperature was reduced and stabilized at about 120°C for 30 minutes. The column was then slowly cooled (0.2°C / min) to 30°C (for ambient operation) or -15°C (for low temperature operation) to crystallize the polymer on the inert support. The low temperature was maintained for 10 minutes before the soluble fraction was injected into the GPC column. All GPC analyses were performed using the solvent o-dichlorobenzene at 1 ml / min, a column temperature of 140°C, and the "overlap GPC injection" mode. Subsequent higher temperature fractions were then analyzed by gradually increasing the TREF column temperature to the fraction set point and allowing the polymer to dissolve for 16 minutes ("analysis time") and injecting the dissolved polymer into the GPC column for 3 minutes ("elution time"). The soluble portion or "purge" of the polymer is not analyzed, only the "insoluble" portion of the polymer sample, ie, the portion that is insoluble at -15°C or below.

[0068] A universal calibration method was used to determine the molecular weight of the eluted polymer. A universal calibration curve was generated using 13 narrow molecular weight distribution polystyrene standards ranging from 1.5 kg / mol to 8,200 kg / mol (obtained from Polymer Labs, UK). Mark-Houwink parameters were obtained from Appendix I of Size Exclusion Chromatography by S. Mori and HG Barth (Springer, 1999). For polystyrene, K = 1.38 x 10 -4 dl / g and α = 0.7; for polyethylene, use K = 5.05x10 -4 dl / g and α = 0.693. Fractions with weight percent recoveries (reported by the instrument software) less than 0.5% were not processed for calculation of molecular weight averages (Mn, Mw, etc.) for each fraction or aggregate of fractions.

[0069] Low temperature cross fractionation (CFC) is used herein to determine molecular weight distribution (MWD) and short chain branching distribution (SCBD) composition information using one or more temperature gradient gel permeation chromatography columns to compare the polymers of the present invention with competitive products on the market. The procedure for interpreting the data obtained from CFC will be discussed in more detail below.

[0070] From the obtained CFC data, each fraction is listed with its cutoff temperature (Ti) and its normalized weight percent (wt%) value, cumulative weight percent and various average molecular weight moments (including weight average molecular weight Mwi).

[0071] like Figure 1 and Figure 2 In the log 10 On the contour plot of MW versus temperature, two peaks were observed for both samples. The peak located at the lower temperature and higher molecular weight portion (corresponding to the low density group) was defined as Peak 1, which had the corresponding temperature and molecular weight coordinates of (Mp1, Tp1). The peak located at the higher temperature and lower molecular weight portion (corresponding to the high density group) was defined as Peak 2, which had the corresponding temperature and molecular weight coordinates of (Mp2, Tp2).

[0072] Quantitatively, the positions of the two peaks and the associated compositional information are calculated using the Moebus Bivariate Deconvolution with Rotation (MBDR) method. MBDR deconvolutes the peaks in x and y (or temperature and molecular weight in this case) using Formula 1 (Pearson IV x Pearson IV) and Formula 2 (Standard Minimization). One of the most important features of this method is the rotation term. Most samples vary in two dimensions simultaneously, but standard deconvolution only allows the dimension parallel to the axis (i.e., x or y but not x and y) to vary. In this case, using standard deconvolution would require fitting more peaks to fully characterize the data. The rotation term allows strictly orthogonal dimensions to rotate, therefore allowing a more accurate characterization of the data. By simultaneously fitting the parameters of two peaks with constraints, such as Figure 1 and Figure 2 As shown in , we can find the peak positions (e.g., molecular weight peak (Mp), temperature peak (Tp)), peak mass fractions (i.e., the area under the graph for each of the two peaks), and shape parameters (e.g., θ).

[0073] Formula 1

[0074]

[0075] in

[0076] x θi =(x-λ xi )cosθ i -(y-λ yi )sinθ i

[0077] y θi =(x-λ xi )sinθ i -(y-λ yi )cosθ i

[0078] Formula 2

[0079] min[(M(x,y)-f(x,y)) 2 ]

[0080] Where M is the measured data or "ground truth".

[0081] Amp: The height of each peak (i.e., z value).

[0082] λ: Position parameter. Indicates the position on the axis where the peak exists.

[0083] α: Scale parameter. Describes the width of the peak (provides Pearson IV definition).

[0084] m: Shape parameter. Describes the kurtosis or "tailing" of the peak.

[0085] ν: shape parameter. Describes the skewness.

[0086] θ: Rotation parameter. Describes the rotation about an orthogonal axis.

[0087] Polyethylene

[0088] The polyethylene of the present invention can be a combination of (1) a polyethylene chain group with a low weight average molecular weight (Mw) and a high density and (2) a polyethylene chain group with a high Mw and a low density. Unless otherwise specified, the polyethylene of the present invention, the polyethylene of the present disclosure or other variants refers to the entire product (i.e., a combination of the two polyethylene chain groups mentioned above).

[0089] The polyethylene of the present disclosure comprises ethylene-derived units and C3-C 12 α-olefin derived units, wherein the C3-C 12 The α-olefin derived units are present in an amount of 0.5 wt% to 10 wt%, alternatively 2 wt% to 10 wt%, or alternatively 5 wt% to 10 wt% of the polyethylene. 12 The α-olefins include 1-butene, 1-hexene, and 1-octene.

[0090] The polyethylene of the present disclosure may have a 3 -0.930g / cm 3 , or alternatively 0.915 g / cm 3 -0.925g / cm 3 density.

[0091] The polyethylene of the present disclosure may have an I2 value of 0.5 g / 10 min to 2 g / 10 min, or alternatively 0.7 g / 10 min to 1 g / 10 min.

[0092] The polyethylene of the present disclosure may have an I of 25 g / 10 min to 75 g / 10 min, or alternatively 30 g / 10 min to 60 g / 10 min. 21 value.

[0093] The polyethylene of the present invention may have an I of 25-75, or alternatively 35-60. 21 / I2 ratio.

[0094] The polyethylene of the present disclosure has an Mw of 95,000 g / mol to 125,000 g / mol, or alternatively 100,000 g / mol to 120,000 g / mol.

[0095] The polyethylene of the present disclosure has a number average molecular weight (Mn) of 10,000 g / mol to 25,000 g / mol, or alternatively 14,000 g / mol to 21,000 g / mol.

[0096] The polyethylene of the present disclosure has a Z average molecular weight (Mz) of 200,000 g / mol to 500,000 g / mol, alternatively 200,000 g / mol to 350,000 g / mol, or alternatively 350,000 g / mol to 500,000 g / mol.

[0097] The polyethylene of the present disclosure has a ratio of Mw to Mn of 4.0 to 9.0, or alternatively 5.0 to 8.0.

[0098] The polyethylene of the present disclosure has a ratio of Mz to Mn of 8-30, or alternatively 10-27.

[0099] The polyethylene of the present disclosure has a molar reverse comonomer index (RCI,m) of 30 kg / mol to 150 kg / mol, alternatively 30 kg / mol to 100 kg / mol, or alternatively 75 kg / mol to 150 kg / mol.

[0100] The polyethylene of the present disclosure has a mol % comonomer distribution ratio (CDR2,m) of 1.0 to 2.0, or alternatively 1.0 to 1.6.

[0101] The polyethylene of the present disclosure may have a phase angle (at 1x10 4 The complex modulus G* value of Pa).

[0102] The polyethylene of the present disclosure may have a θ2 in the range of 1.5 radians to -1.5 radians.

[0103] Method for preparing polyethylene

[0104] The polyethylene of the present disclosure is synthesized using a mixed catalyst comprising a rac-dimethylsilylbis(tetrahydroindenyl)zirconium dichloride catalyst according to compound I and a zirconium co-catalyst that is a poor comonomer binder compared to the rac-dimethylsilylbis(tetrahydroindenyl)zirconium dichloride catalyst (e.g., meso-1,1,3,3-tetramethyldisiloxy-1,3-diindenyl zirconium dichloride according to compound II or (1-methylindenyl)(pentamethylcyclopentadienyl)zirconium dimethyl (compound III). Other poor comonomer binders can be found in U.S. Patent No. 6,828,394, which is incorporated herein by reference.

[0105]

[0106] Typically, the racemic-dimethylsilylbis(tetrahydroindenyl)zirconium dichloride catalyst and the zirconium co-catalyst are mixed to form a uniform suspension of the catalyst, which is then deposited on an inert support. The molar ratio of the racemic-dimethylsilylbis(tetrahydroindenyl)zirconium dichloride catalyst to the zirconium co-catalyst may be in the range of 50:50-90:10, or alternatively in the range of 55:45-85:15.

[0107] The mixed catalyst system may be free of activators. The term "activator" as used herein refers to a compound capable of converting a catalyst precursor into an active polymerization catalyst, and preferably comprises an alkylaluminoxane compound (e.g., methylaluminoxane) and / or tetrakis(perfluoroaryl)borate, but more preferably comprises tetrakis(perfluoroaryl)borate. Even more preferably, the activator comprises an anionic activator selected from the group consisting of tetrakis(pentafluorophenyl)borate, tetrakis(perfluorobiphenyl)borate, tetrakis(perfluoronaphthyl)borate, and combinations thereof.

[0108] The inert support preferably comprises silicon dioxide, such as amorphous silicon dioxide, which may include a hydrated surface presenting hydroxyl groups or other groups that may be deprotonated to form reactive sites to anchor activators and / or catalyst precursors. Other porous support materials may optionally be present as co-supports with silicon dioxide, such as talc, other inorganic oxides, zeolites, clays, organoclays, or any other organic or inorganic support materials, or mixtures thereof. Possibly suitable silicon dioxide may be commercially available under the trade names PD 14024 (PQ Corporation), D70-120A (Asahi Glass Co., Ltd. or AGC Chemicals Americas, Inc.), etc.

[0109] The inert support preferably comprises silicon dioxide, such as amorphous silicon dioxide, which may include a hydrated surface presenting hydroxyl groups or other groups that may be deprotonated to form reactive sites to anchor activators and / or catalyst precursors. Other porous support materials may optionally be present as co-supports with silicon dioxide, such as talc, other inorganic oxides, zeolites, clays, organoclays, or any other organic or inorganic support materials, or mixtures thereof. Possibly suitable silicon dioxide may be commercially available under the trade names PD 14024 (PQ Corporation), D70-120A (Asahi Glass Co., Ltd. or AGC Chemicals Americas, Inc.), etc.

[0110] The inert support is preferably dry, that is to say free of absorbed water. Drying of the inert support may be carried out by heating or calcining at 130° C. to 850° C., or alternatively 200° C. to 600° C. for a period of 1 minute to 100 hours, alternatively 12 hours to 72 hours, or alternatively 24 hours to 60 hours. The calcined support material may contain at least some groups capable of reacting with the metal organic compound used to produce the supported catalyst system of the present invention, such as reactive hydroxyl (OH) groups.

[0111] Polyethylene can be produced in any known method, for example slurry (in solution) method, for example in so-called "loop" reactor well known in the art, or in gas phase reactor, especially fluidized bed gas phase reactor, wherein monomer and other gases are circulated through the bed of polymer. Polyethylene is preferably produced in a gas phase process with a gas velocity of 1 ft / sec to 4 ft / sec, or alternatively 1 ft / sec to 2 ft / sec. Such method is well known in the art, and the method for making polyethylene is not subject to other special restrictions.

[0112] The polyethylene of the present disclosure can be produced in a single reactor process, where the monomer is contacted with the catalyst in only one reactor to produce the polyethylene, or the polyethylene of the present disclosure can be produced in a dual reactor process, where the monomer is contacted with the catalyst in two or more reactors connected in parallel or in series, but a single reactor process is most preferred.

[0113] The method for producing the polyethylene of the present disclosure generally comprises reacting ethylene, C3-C 12 The alpha-olefin comonomer and hydrogen react in the presence of the mixed catalyst.

[0114] The reaction temperature for producing the polyethylene of the present disclosure may be from 66°C (150°F) to 93°C (200°F), or alternatively from 77°C (170°F) to 88°C (190°F).

[0115] The reactor pressure when producing the polyethylene of the present disclosure may be from 200 psig to 400 psig, or alternatively from 250 psig to 350 psig.

[0116] When producing the polyethylene of the present disclosure, the mole % ratio of comonomer to ethylene in the reactor may be from 0.005 to 0.030, or alternatively from 0.005 to 0.020.

[0117] When producing the polyethylene of the present disclosure, the ratio of the ppm of hydrogen to the mole % of ethylene in the reactor may be from 3.0 to 20.0, or alternatively from 4.0 to 15.0.

[0118] Polyethylene film

[0119] The polyethylene of the present disclosure can be used to produce films. The film can be formed by any known process, but is preferably formed by "blowing" in a blown film process. The final film can be a monolayer film, which comprises the polyethylene of the present disclosure blended with other polymers, especially other polyolefins, or it is basically composed of the polyethylene of the present disclosure and common additives such as antioxidants, fillers, etc. The film can also comprise two, three, four, five or more layers, any one or more of which can comprise the polyethylene of the present disclosure or be basically composed of the polyethylene of the present disclosure. When the layer of the film comprises the polyethylene of the present disclosure, it can be used as a blend with other polyolefins such as low density polyethylene, linear low density polyethylene, high density polyethylene, polypropylene homopolymer, polypropylene copolymer and combinations thereof.

[0120] In a typical process, a polyethylene melt is extruded vertically through a die such as an annular slot die to form a thin-walled tube. Cooling (preferably in the form of positive air pressure) is introduced through a device in the center of the die to inflate the tube like a balloon. Cooling can also be achieved by other measures or accompanied by other measures such as external (for the film) devices, and the gas can be nitrogen / oxygen or other gases or a mixture of gases or liquids. For example, a high-speed air ring installed on the top of the die blows to the outside of the hot film to cool it. The cooling can occur at some adjustable distance from the die, which is usually at least 1 cm away from the die of the melt extrusion. Then, the film tube can continue to move upward or away from the die in the "longitudinal direction" (MD), continuing to cool until it can pass through a press roller, where the tube is flattened to form a so-called "laid-flat" film tube. This flat or folded tube can then be retracted from the extrusion "tower" through more rollers. At higher output lines, the air in the bubble is also exchanged. This is called IBC (inter-bubble cooling).

[0121] More specifically, in the blown film process, the ingredients for forming the film are added in any desired form (preferably in the form of granules) to a hopper that feeds the material to one or more extruders, where the material is melt blended at a desired temperature by shearing forces and / or heating. The molten material is then fed into a die that is also heated to a desired temperature, such as 180°C to 220°C, with or without filtering, and then forced out of the die at least in part by the force of the blown air in a direction away from the die. The cooling of the formed film occurs as the film moves away from the die, and a high-speed air ring that preferably blows air that is at least 10°C cooler than the surrounding air or at least 20°C helps the cooling. Preferably, the ambient temperature of the area where the film is formed is 20°C to 60°C, or 30°C to 50°C. Most preferably, the formed film is cylindrical, and the air ring forms a ring around the cooling tube that blows air concentrically around the film. The air is preferably blown to the outside of the film, most preferably around the entire circumference formed by the film. The distance between the device and the die opening can be varied to allow "relaxation time" for the hot film to gradually cool before being exposed to the cooling air from the cooling device. There is also internal blown air, which both cools the film and blows it up like a balloon. The film begins to expand, eventually cools and crystallizes to form the finished blown film, which is finally separated by various means such as rollers, nips, etc.

[0122] The lay-flat film is then either left as is or the edges of the lay-flat film are cut to produce two flat film sheets and wound onto reels. Articles such as bags can be made from such lay-flat film. In this regard, if left lay-flat, the film tube can be made into bags by sealing across the width of the film and cutting or perforating to make each bag. This can be done in-line during the blown film process or at a later stage.

[0123] Preferably, the expansion ratio between the die and the blown film tube will be 1.5 to 4 times the die diameter. The drop between the melt wall thickness and the cooled film thickness occurs in both radial and longitudinal directions and is easily controlled by varying the air volume within the bubble and by varying the draw speed. This gives a better balance of properties to blown film than conventional cast film or extruded film that stretches only in the extrusion direction.

[0124] Preferably, the die used to form the film herein is designed so that the die opening through which the molten polyolefin is extruded is in the form of a ring, and the molten polyolefin flowing out therefrom is in the form of a continuous tube. The die productivity (Die Factor Rate) of the film is in the range of 10 pounds / inch hours (0.56 kilograms / millimeter hours) to 40 pounds / inch hours (2.25 kilograms / millimeter hours), or alternatively in the range of 15 pounds / inch hours (0.84 kilograms / millimeter hours) to 26 pounds / inch hours (1.46 kilograms / millimeter hours); and preferably, the maximum extrusion rate is in the range of 350 pounds / hour (159 kilograms / hour) to 500 pounds / hour (227 kilograms / hour). Please note that there is a difference in addition to the unit regarding the "die factor". In imperial units, the die size is the die circumference, while in metric units, the die size is the die diameter.

[0125] Films comprising or consisting essentially of the polyethylene of the present disclosure may have an average thickness in the range of 10 μm-100 μm, alternatively 15 μm-60 μm, or alternatively 15 μm-40 μm.

[0126] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a machine direction (MD) 1% secant flexural modulus of 25,000-45,000 psi, or alternatively 30,000-45,000 psi.Regarding the MD 1% secant flexural modulus, higher values ​​indicate higher toughness of the film.

[0127] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a transverse direction (TD, perpendicular to MD in the plane of the film) 1% secant flexural modulus of 30,000 psi to 60,000 psi, or alternatively 35,000 psi to 56,000 psi. With respect to the transverse direction 1% secant flexural modulus, higher values ​​indicate higher toughness of the film.

[0128] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a machine direction tensile yield strength of 1,000 psi to 2,000 psi, or alternatively 1,250 psi to 1,750 psi.

[0129] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a TD tensile yield strength of 1,000 psi to 2,500 psi, or alternatively 1,500 psi to 2,500 psi.

[0130] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a machine direction elongation at yield of 5% to 12%, or alternatively 7% to 12%.

[0131] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a TD elongation at yield of 4% to 9%, or alternatively 5% to 9%.

[0132] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a machine direction tensile strength of 5,000 psi to 10,000 psi, or alternatively 6,000 psi to 9,000 psi.

[0133] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a TD tensile strength of 5,000 psi to 10,000 psi, or alternatively 6,000 psi to 9,000 psi.

[0134] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a machine direction elongation at break of 400% to 550%, or alternatively 450% to 550%.

[0135] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a TD elongation at break of 500% to 700%, or alternatively 550% to 700%.

[0136] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a machine direction Elmendorf Tear of 40g-150g, or alternatively 50g-125g. With respect to the machine direction Elmendorf Tear, higher values ​​indicate higher toughness of the film.

[0137] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a TD Elmendorf Tear of 450g-625g, or alternatively 500g-625g.Regarding the transverse direction Elmendorf Tear, higher values ​​indicate higher toughness of the film.

[0138] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a haze of 5% to 30%, or alternatively 10% to 25%.

[0139] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a machine direction gloss of 20% to 60%, or alternatively 25% to 50%.

[0140] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a TD gloss of 20%-60%, or alternatively 25%-50%.

[0141] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a dart drop impact value of 200 g / mil to 750 g / mil, or alternatively 300 g / mil to 600 g / mil.

[0142] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a seal initiation temperature of 100°C to 120°C, or alternatively 100°C to 110°C at 1 N force.

[0143] Films comprising or consisting essentially of the polyethylene of the present disclosure may have a maximum hot tack of 5N-20N, preferably 10N-17N.

[0144] When referring to polyethylene or polyethylene film herein, in any embodiment, when the phrase "essentially consisting of..." is used, it means that the polyethylene or the film made of polyethylene includes less than 5wt% or 4wt% or 3wt% or 2wt% or 1wt% (based on the weight of the polyethylene) of additives known in the art, such as fillers, colorants, antioxidants, anti-UV additives, curing agents and cross-linking agents, aliphatic and / or cyclic oligomers or polymers commonly known as hydrocarbon polyethylene and other additives well known in the art, as well as other common additives, such as those disclosed in WO 2009 / 007265.

[0145] Example Implementation

[0146] A non-limiting example embodiment of the present disclosure is a method comprising: reacting ethylene, C3 to C 12 An alpha-olefin comonomer and hydrogen are reacted in the presence of a mixed catalyst to form a polyethylene, wherein the polyethylene comprises ethylene-derived units and C3-C4-C6-H2O in an amount of 0.5 wt % to 10 wt % of the polyethylene. 12 α-olefin derived units, wherein the polyethylene has: 0.91 g / cm 3 -0.93g / cm 3 Density, I2 value in the range of 0.5g / 10min-2g / 10min, I in the range of 25g / 10min-75g / 10min 21 Value, 25-75 I 21 / I2 ratio, a molar reverse comonomer index (RCI,m) of 30-180, a phase angle equal to or lower than 70° at a complex modulus G* of 10,000 Pa, θ2 in the range of 1.5 radians to -1.5 radians, and a low density population in the range of 50 wt% to 70 wt% of the polyethylene; and wherein the mixed catalyst comprises racemic-dimethylsilylbis(tetrahydroindenyl)zirconium dichloride (Compound I) and a zirconium co-catalyst (Compound II), the molar ratio of Compound I to Compound II being 50:50 to 90:10, and wherein the zirconium co-catalyst is a poor comonomer binder compared to the racemic-dimethylsilylbis(tetrahydroindenyl)zirconium dichloride catalyst. The reaction conditions may include one or more of the following: wherein the reaction temperature is from 66°C (150°F) to 93°C (200°F); wherein the reactor pressure is from 200 psig to 400 psig; wherein the mole % ratio of comonomer to ethylene in the reactor is from 0.005 to 0.030; and wherein the mole % ratio of hydrogen to ethylene in the reactor is from 3.0 to 5.5.

[0147] Another non-limiting example embodiment is a film comprising: a C3-C6 polyethylene having ethylene-derived units and an amount of 0.5 wt % to 10 wt % of the polyethylene. 12 A polyethylene containing alpha-olefin derived units, the polyethylene having: 0.91 g / cm 3 -0.93g / cm 3 Density, I2 value in the range of 0.5g / 10min-2g / 10min, I in the range of 25g / 10min-75g / 10min 21 Value, 25-75 I 21 / I2 ratio, a molar reverse comonomer index (RCI,m) of 30-180, a phase angle equal to or less than 70° at a complex modulus G* of 10,000 Pa, θ2 in the range of 1.5 radians to -1.5 radians, and a low density population in the range of 50 wt% to 70 wt% of the polyethylene; wherein the film has a machine direction (MD) 1% secant flexural modulus of 25,000 psi to 45,000 psi, a machine direction Elmendorf tear of 200 g to 350 g, and a dart drop impact value of 200 g / mil to 1,000 g / mil. The film may also have one or more of the following properties: wherein the film has a longitudinal tensile yield strength of 1,000psi-2,000psi; wherein the film has a TD 1% secant flexural modulus of 30,000psi-60,000psi; wherein the film has a TD tensile yield strength of 1,000psi-2,500psi; wherein the film has a longitudinal elongation at yield of 5%-12%; wherein the film has a longitudinal tensile strength of 5,000psi-10,000psi; and wherein the film has a longitudinal elongation at break of 400%-550%.

[0148] Yet another non-limiting example of the present disclosure is a composition comprising: a C3-C6-ethylene-containing unit and an amount of 0.5 wt % to 10 wt % of the polyethylene; 12 A polyethylene containing alpha-olefin derived units, the polyethylene having: 0.91 g / cm 3 -0.93g / cm 3 Density, I2 value in the range of 0.5g / 10min-2g / 10min, I in the range of 25g / 10min-75g / 10min 21 Value, 25-75 I 21 / I2 ratio, a molar reverse comonomer index (RCI,m) of 30-180, a phase angle equal to or lower than 70° at a complex modulus G* of 10,000 Pa, θ2 in the range of 1.5 radians to -1.5 radians, and a low density population in the range of 50 wt% to 70 wt% of the polyethylene.

[0149] Optionally, any of the foregoing non-limiting examples may further include one or more of the following elements: Element 1: wherein the polyethylene has a weight average molecular weight (Mw) of 95,000 g / mol-125,000 g / mol; Element 2: wherein the polyethylene has a number average molecular weight (Mn) of 10,000 g / mol-25,000 g / mol; Element 3: wherein the polyethylene has a Z average molecular weight (Mz) of 200,000 g / mol-500,000 g / mol; Element 4: wherein the polyethylene has a Mw to Mn ratio of 4.0-9.0; Element 5: wherein the polyethylene has a Mz to Mn ratio of 8-30; and Element 6: wherein the polyethylene has a mol % comonomer distribution ratio (CDR2,m) of 1.0-2.0. Examples of combinations include, but are not limited to: a combination of element 1 with one or more of elements 2-6; a combination of element 2 with one or more of elements 3-6; a combination of element 3 with one or more of elements 4-6; a combination of element 4 with one or more of elements 5-6; and a combination of elements 5 and 6.

[0150] Unless otherwise indicated, all numbers used in this specification and the associated claims expressing the amounts of ingredients, properties such as molecular weight, reaction conditions, etc. should be understood as being modified in all instances by the term "about". Therefore, unless indicated to the contrary, the numerical parameters set forth in the following specification and the appended claims are approximate values ​​that can vary depending on the desired properties sought to be obtained by the embodiments of the present invention. At the very least, and without attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be interpreted in light of the number of reported significant digits and by applying ordinary rounding techniques.

[0151] One or more illustrative embodiments in conjunction with the embodiments of the present invention disclosed herein are presented here. For the sake of clarity, all features of physical implementation are not described or shown in this application. It should be understood that in the development of the physical implementation in conjunction with the embodiments of the present invention, many decisions specific to implementation must be made to realize the target of the developer, such as meeting the constraints related to the system, the constraints related to the business, the constraints related to the government and other constraints, which vary due to specific implementation and opportunity. Although the efforts of the developer may be time consuming, such efforts will be routine work for those of ordinary skill in the art who benefit from the disclosure.

[0152] Although compositions and methods are described herein as "comprising" various components or steps, the compositions and methods may also "consist essentially of" or "consist of" the various components and steps.

[0153] In order to help better understand the embodiments of the present invention, the following examples of preferred or representative embodiments are given. The following examples should in no way be understood to limit or define the scope of the present invention. Example

[0154] Mixed catalyst 1 - 80:20 weight ratio of racemic dimethylsilylbis(tetrahydroindenyl)zirconium dichloride (Compound I) and meso-1,1,3,3-tetramethyldisiloxy-1,3-diindenylzirconium dichloride (Compound II).

[0155] To a stirred vessel was added 1,400 g of toluene and 925 g of methylaluminoxane (30 wt % in toluene). To this solution was added 734 g of ES70–875°C calcined silica. The mixture was then stirred at 100°C for 3 hours before the temperature was reduced and the reaction allowed to cool to ambient temperature. Racemic dimethylsilylbis(tetrahydroindenyl)zirconium dichloride (14.62 g, 32.00 mmol) and meso-1,1,3,3-tetramethyldisiloxy-1,3-diindenylzirconium dichloride (4.18 g, 8.00 mmol) were then dissolved in toluene (250 g) and added to the vessel and stirred for another two hours. The mixing speed was then reduced and stirred slowly for 60 hours while vacuum drying, after which 1,012 g of light yellow silica was obtained.

[0156] Mixed catalyst 2 - 60:40 weight ratio of racemic dimethylsilylbis(tetrahydroindenyl)zirconium dichloride (Compound I) and meso-1,1,3,3-tetramethyldisiloxy-1,3-diindenylzirconium dichloride (Compound II).

[0157] 1,400 g of toluene and 925 g of methylaluminoxane (30 wt % in toluene) were added to a stirred container. 734 g of ES70–875°C calcined silica was added to the solution. The mixture was then stirred at 100°C for 3 hours, then the temperature was reduced and the reaction was allowed to cool to ambient temperature. Racemic dimethylsilylbis(tetrahydroindenyl)zirconium dichloride (10.96 g, 24.00 mmol) and meso-1,1,3,3-tetramethyldisiloxy-1,3-diindenylzirconium dichloride (8.36 g, 16.0 mmol) were then dissolved in toluene (250 g) and added to the container and stirred for another two hours. The mixing speed was then reduced and stirred slowly for 60 hours while vacuum drying, after which 1,041 of light yellow silica was obtained.

[0158] Mixed catalyst 3 - racemic dimethylsilylbis(tetrahydroindenyl)zirconium dichloride (Compound I) and (1-methylindenyl)(pentamethylcyclopentadienyl)zirconium dimethyl (Compound III) in a 80:20 weight ratio.

[0159] 1,400 g of toluene and 925 g of methylaluminoxane (30 wt % in toluene) were added to a stirred vessel. 734 g of ES70–875°C calcined silica was added to the solution. The mixture was then stirred at 100°C for 3 hours, then the temperature was reduced and the reaction was allowed to cool to ambient temperature. Racemic dimethylsilylbis(tetrahydroindenyl)zirconium dichloride (14.62 g, 32.00 mmol) and (1-methylindenyl)(pentamethylcyclopentadienyl)zirconium dimethylate (3.09 g, 8.00 mmol) were then dissolved in toluene (250 g) and added to the vessel and stirred for another two hours. The mixing speed was then reduced and stirred slowly for 60 hours while vacuum drying, after which 1,011 of light yellow silica was obtained.

[0160] The polymerization was carried out in an 18.5 foot tall gas phase fluidized bed reactor having a 10 foot main body and an 8.5 foot expansion section. The recycle and feed gases entered the reactor main body through a porous distribution plate and the reactor was controlled at 300 psi and 64 mol% ethylene. The reactor temperature was maintained at 85°C (185°F) throughout the polymerization by controlling the temperature of the recycle gas loop. The catalyst was delivered as a mineral oil slurry containing 20 wt% of the supported catalyst. As a control, racemic dimethylsilylbis(tetrahydroindenyl)zirconium dichloride (Compound I) on the same support as above was used as the catalyst (single catalyst for comparison). Table 2 provides the process conditions used to produce polyethylene.

[0161] Table 2

[0162]

[0163]

[0164] Tables 3 and 4 provide the polyethylene product properties.

[0165] Table 3

[0166] sample MC1 MC2 MC3 <![CDATA[I2(g / 10min)]]> 0.59 0.80 1.11 <![CDATA[I 21 (g / 10min)]]> 23.30 46.98 59.78 <![CDATA[I 21 / I2]]> 39.67 58.40 53.69 <![CDATA[Density (g / cm 3 )]]> 0.9198 0.9228 0.9231

[0167] Table 4

[0168]

[0169]

[0170] In each case, the addition of the meso-1,1,3,3-tetramethyldisiloxy-1,3-diindenyl zirconium reduced the overall binding capacity of the system, as shown by the increased hexene requirement to produce a product of the same density. The reduced hydrogen requirement also shows the reduced molecular weight capacity of the meso-1,1,3,3-tetramethyldisiloxy-1,3-diindenyl zirconium compared to the racemic dimethylsilylbis(tetrahydroindenyl) zirconium. Thus, the introduction of the meso-1,1,3,3-tetramethyldisiloxy-1,3-diindenyl zirconium into the system contributes a low molecular weight, high density component. At similar temperatures of 87°C (188°F) and 85°C (185°F), when this component was added to the system, the molecular weight of the product increased. 21 Increasing the loading of meso-1,1,3,3-tetramethyldisiloxy-1,3-diindenyl zirconium catalyst from 20 mol% to 40 mol% further increased this I 21 / I2 shifts due to more low molecular weight, high density components. Similarly, more hexene and less hydrogen are required to meet the target specifications. When the temperature is reduced to 79°C (175°F) at a ratio of 80:20, the I 21 / I2 was adjusted to similar values, indicating a possible shift in the molecular weight distribution that could lead to more favorable film properties.

[0171] Changing the co-catalyst to (1-methylindenyl) (pentamethylcyclopentadiene) zirconium further increased the molecular weight and density differences between the two components in the system. Compared with all tested rac-dimethylsilylbis(tetrahydroindenyl) zirconium dichloride / meso-1,1,3,3-tetramethyldisiloxy-1,3-bisindenyl zirconium dichloride systems, the hydrogen demand was lower and the hexene demand was higher. At a catalyst ratio of 80:20, the (1-methylindenyl) (pentamethylcyclopentadiene) zirconium system also showed higher I than the meso-1,1,3,3-tetramethyldisiloxy-1,3-bisindenyl zirconium dichloride system. 21 / I2. This difference is most likely due to the larger molecular weight difference between the two components.

[0172] Figure 1 and 2 is the CFC data of MC2 and MC3. Table 5 is the CFC data of MC2 and MC3 using the MBDR method. Figure 1 and 2 Deconvoluted molecular weight data. In Table 5, the cumulative Wt% 过渡 is defined as the average cumulative wt% separating the two population contours, i.e. the location of the saddle line. Orientation P1 represents the orientation of the low-density peak, while the orientation P2Indicates the orientation of the high density peak. Positive orientation values ​​indicate that the composition distribution of the peak is BOCD, and negative orientation values ​​indicate that the composition distribution of the peak is BCD. Orientation values ​​close to 0 or 180 indicate a narrow composition distribution and a broad MW distribution, while an orientation of about 90 indicates a narrow MW distribution and a broad composition distribution. Comparative CFC data are taken from PE resins prepared as described in US 2019-0144576.

[0173] Table 5

[0174]

[0175] Blown film was extruded on a 2.5" Battenfield Gloucester line (30:1 L:D) equipped with a 6" oscillating die. The production rate was 188 lbs / hr (10 lbs / hr / inch die circumference) and the die gap was 60 mils. The target film gauge was 1 mil and the blow-up ratio was kept constant at 2.5. The FLH was typically 19-24 inches. A standard "hump" temperature profile was used where "BZ" is the barrel zone: BZ1 = 310 / BZ2 = 410 / BZ3 = 380 / BZ4 = 350 / BZ5 = 350 / adapter = 390 / die = 390F.

[0176] Table 6

[0177]

[0178]

[0179] Further process data including film performance at 1.0 mil gauge can be found in Table 6. TDA is Total Defect Area, which is a measure of defects in a film sample and is reported as the area of ​​film inspected in square meters (m2). 2 ))Normalized cumulative defect area (in square millimeters (mm) 2 )), so it has the unit (mm 2 / m 2) or "ppm". Only defects with a size greater than 200 microns are reported in Table 6. TDA is obtained by an optical control system (Optical Control System, OCS). The system includes a small extruder (ME20 2800), a cast film die, a cooling roll unit (CR-9 model), a winding system with good film tension control, and an online camera system (FSA-100 model) for inspecting optical defects produced by cast films. Typical test conditions for cast film production include extruder zone temperature settings of 154-210°C; feed throat / zone 1 / zone 2 / zone 3 / zone 4 / die of 70 / 190 / 200 / 210 / 215 / 215; extruder speed of 50 rpm; cooling roll temperature of 30°C; and cooling roll speed of 3.5 m / min. The system produces cast films with a width of approximately 4.9 inches and a nominal specification of 2 mil. The melt temperature varies with the material and is typically about 215°C. ESO is the specific energy extrusion output (lb / hr) normalized by the extruder power (hp) consumption in film extrusion and is a measure of the material processability.

[0180] Table 7 provides the properties of the films.

[0181] Table 7

[0182]

[0183]

[0184] Table 7 (continued)

[0185]

[0186] Therefore, the present invention is well suited to achieve the mentioned purposes and advantages and those inherent therein. The specific embodiments disclosed above are illustrative only, because the present invention can be modified and practiced in different but obvious equivalent ways to those skilled in the art who benefit from the teachings herein. In addition, except as described in the claims below, it is not intended to limit the details of the construction or design shown here. It is therefore obvious that the specific illustrative embodiments disclosed above can be changed, combined or modified, and all such changes are considered to be within the scope and spirit of the present invention. The present invention disclosed illustratively in this article can be appropriately implemented without any elements not specifically disclosed herein and / or any optional elements disclosed in this article. Although compositions and methods are described in a manner of "comprising", "containing" or "including" various components or steps, the compositions and methods can also be "essentially composed of" or "composed of" the various components and steps. All numbers and ranges disclosed above can vary to some extent. Whenever a numerical range with a lower limit and an upper limit is disclosed, any number and any included range falling within the range are specifically disclosed. In particular, each numerical range disclosed herein (in the form of "from about a to about b", or equivalently "about from a to b", or equivalently "about ab") should be understood to set forth each number and range contained in the broader numerical range. In addition, unless otherwise explicitly and clearly defined by the patentee, the terms in the claims have their plain, ordinary meanings. In addition, the indefinite articles "a" or "an" used in the claims are defined herein to mean one or more of the elements they introduce.

Claims

1. A method, comprising: Ethylene, C3 to C 12 An alpha-olefin comonomer and hydrogen are reacted in the presence of a mixed catalyst to form a polyethylene, wherein the polyethylene comprises ethylene-derived units and C3-C4-C6-H2O in an amount of 0.5 wt % to 10 wt % of the polyethylene. 12 α-olefin derived units, wherein the polyethylene has: 0.91g / cm 3 -0.93g / cm 3 The density, measured according to ASTM D1505-18, I2 values ​​in the range of 0.5 g / 10 min - 2 g / 10 min, measured according to ASTM D1238-13 at 2.16 kg and 190°C, In the range of 25g / 10min-75g / 10min 21 Values, measured according to ASTM D1238-13 at 21.6 kg and 190°C, 25-75 I 21 / I2 ratio, A molar reverse comonomer index (RCI,m) of 30-180, measured by cross-fractionation chromatography, A phase angle equal to or lower than 70° at a complex modulus G* of 10,000 Pa, as measured by a small angle oscillatory shear rheology test, θ2 in the range of 1.5 rad to -1.5 rad, as measured by cross-fractionation chromatography, and a low density population in the range of 50% to 70% by weight of said polyethylene as measured by cross fractionation chromatography; and The mixed catalyst comprises racemic-dimethylsilylbis(tetrahydroindenyl)zirconium dichloride (Compound I) and a zirconium co-catalyst (Compound II), the molar ratio of Compound I to Compound II being 50:50-90:10, and wherein the zirconium co-catalyst is a poor comonomer binder compared to the racemic-dimethylsilylbis(tetrahydroindenyl)zirconium dichloride catalyst.

2. The method of claim 1, wherein the reaction is carried out at a temperature of 66°C-93°C.

3. The method of claim 1, wherein the reaction is carried out at a pressure of 200 psig to 400 psig.

4. The process of claim 1, wherein the reaction is carried out in a reactor wherein the mole % ratio of comonomer to ethylene in the reactor is in the range of 0.005-0.

030.

5. The process of claim 1, wherein the reaction is carried out in a reactor wherein the mole % ratio of hydrogen to ethylene in the reactor is in the range of 3.0-5.

5.

6. The method of any one of claims 1-5, wherein the polyethylene further has one or more of the following properties: (a) a weight average molecular weight (Mw) of 95,000 g / mol to 125,000 g / mol, as measured by 4D GPC; (b) a number average molecular weight (Mn) of 10,000 g / mol to 25,000 g / mol, as measured by 4D GPC; (c) a Z-average molecular weight (Mz) of 200,000 g / mol to 500,000 g / mol, as measured by 4D GPC; (d) a ratio of Mw to Mn (Mw / Mn) in the range of 4.0-9.0; (e) a ratio of Mz to Mn (Mz / Mn) in the range of 8-30; and (f) a mol % comonomer distribution ratio (CDR2,m) of 1.0-2.

0.

7. The method of claim 6, wherein the polyethylene has all of the properties (a) - (f).

8. The method of claim 6, further comprising forming a film from the compound comprising the polyethylene.

9. A film comprising: C3-C6-H2O-2 containing ethylene-derived units and an amount of 0.5 wt % to 10 wt % of the polyethylene 12 A polyethylene containing alpha-olefin derived units, the polyethylene having: 0.91g / cm 3 -0.93g / cm 3 The density, measured according to ASTM D1505-18, I2 values ​​in the range of 0.5 g / 10 min - 2 g / 10 min, measured according to ASTM D1238-13 at 2.16 kg and 190°C, In the range of 25g / 10min-75g / 10min 21 Values, measured according to ASTM D1238-13 at 21.6 kg and 190°C, 25-75 I 21 / I2 ratio, A molar reverse comonomer index (RCI,m) of 30-180, measured by cross-fractionation chromatography, A phase angle equal to or lower than 70° at a complex modulus G* of 10,000 Pa, as measured by a small angle oscillatory shear rheology test, θ2 in the range of 1.5 rad to -1.5 rad, as measured by cross-fractionation chromatography, and a low density population in the range of 50% to 70% by weight of said polyethylene as measured by cross fractionation chromatography; and wherein the film has a machine direction (MD) 1% secant flexural modulus of 25,000 psi to 45,000 psi, measured according to ASTM D882-18, 15 mm width strip; a machine direction Elmendorf tear of 40 g to 150 g, measured according to ASTM D1922-15; and a dart drop impact value of 200 g / mil to 1,000 g / mil, measured according to ASTM D1709-16a1, Method A.

10. The film of claim 9, wherein the film has one or more of the following properties: (i) 1,000 psi to 2,000 psi longitudinal tensile yield strength, measured in accordance with ASTM D882-18, 15 mm width strip; (ii) TD 1% secant flexural modulus of 30,000 psi to 60,000 psi, measured according to ASTM D882-18, 15 mm width bar; (iii) TD tensile yield strength of 1,000 psi to 2,500 psi, measured in accordance with ASTM D882-18, 15 mm width bar; (iv) 5% to 12% longitudinal elongation at yield, measured according to ASTM D882-18, 15 mm width strip; (v) a longitudinal tensile strength of 5,000 psi to 10,000 psi, measured in accordance with ASTM D882-18, 15 mm width strips; and (vi) 400% to 550% longitudinal elongation at break, measured according to ASTM D882-18, 15 mm width strip.

11. A composition comprising: C3-C6-ethylene-derived units and an amount of 0.5 wt% to 10 wt% of the polyethylene 12 A polyethylene containing alpha-olefin derived units, the polyethylene having: 0.91g / cm 3 -0.93g / cm 3 The density, measured according to ASTM D1505-18, I2 values ​​in the range of 0.5 g / 10 min - 2 g / 10 min, measured according to ASTM D1238-13 at 2.16 kg and 190°C, In the range of 25g / 10min-75g / 10min 21 Values, measured according to ASTM D1238-13 at 21.6 kg and 190°C, 25-75 I 21 / I2 ratio, A molar reverse comonomer index (RCI,m) of 30-180, measured by cross-fractionation chromatography, A phase angle equal to or lower than 70° at a complex modulus G* of 10,000 Pa, as measured by a small angle oscillatory shear rheology test, θ2 in the range of 1.5 rad to -1.5 rad, as measured by cross-fractionation chromatography, and A low density population in the range of 50% to 70% by weight of the polyethylene as measured by cross fractionation chromatography.

12. The composition of claim 11, wherein the polyethylene further has one or more of the following properties: (a) a weight average molecular weight (Mw) of 95,000 g / mol to 125,000 g / mol, as measured by 4D GPC; (b) a number average molecular weight (Mn) of 10,000 g / mol to 25,000 g / mol, as measured by 4D GPC; (c) a Z-average molecular weight (Mz) of 200,000 g / mol to 500,000 g / mol, as measured by 4D GPC; (d) a ratio of Mw to Mn (Mw / Mn) in the range of 4.0-9.0; (e) a ratio of Mz to Mn (Mz / Mn) in the range of 8-30; and (f) a mol % comonomer distribution ratio (CDR2,m) of 1.0-2.

0.

13. The composition of claim 12, wherein the polyethylene has all of the properties (a) - (f).

Citation Information

Patent Citations

  • Polyethylene Compositions and Articles Made Therefrom

    US20190144576A1

  • Mixed metallocene catalyst systems containing a poor comonomer incorporator and a good comonomer incorporator

    US6828394B2

  • Stabilizer compositions

    WO2009007265A1

  • Producing polyethylene products with improved stiffness, toughness, and processability

    WO2015123164A1

  • Polyethylene compositions and articles made therefrom

    WO2019083609A1